Antioxidant Activity and Properties of Walnut Brown Seed Coat Extract - Majid Asadi Samani (Journal of Global Pharma Technology, 2017)
To date, there are few studies about the properties of walnut brown seed coat. The antioxidant activity and properties of walnut brown seed coat was considered in this study and the amounts of carotenoids, chlorophylla, chlorophyllb, vitamin E were determined. The antioxidant activity was determined by cupric assay, DPPH, and measurement of oxidative stability in sunflower oil against Copper sulfate. Walnut brown seed coat at 1% was effective antioxidant in comparison to BHT in inhibition of lipid peroxidation. This extract presented the highest vitamin E level (1.4± 0.042 mg/g). DPPH assay showed the extract had the high radical scavenging ability. The results of this study showed the walnut brown seed coat possessed strong antioxidant properties in vitro, hence it might be beneficial in human health. Keywords: Walnut, Antioxidant activity, Vitamin E, Cartenoids, Chlorophylls.